2017
DOI: 10.3389/fmicb.2017.02152
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Simultaneous Onset of Viral Gene Expression Among Cells Infected with Herpes Simplex Virus-1

Abstract: Synchronous viral infection facilitates the study of viral gene expression, viral host interactions, and viral replication processes. However, the protocols for achieving synchronous infections were hardly ever tested in proper temporal resolution at the single-cell level. We set up a fluorescence-based, time lapse microscopy assay to study sources of variability in the timing of gene expression during herpes simplex virus-1 (HSV-1) infection. We found that with the common protocol, the onset of gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…In vitro experiments have previously shown that HSV-1 infection at differing MOI yields differential viral gene transcription rates [ 26 , 47 ]. Using our model, we sought to evaluate whether the virus can mitigate the effects of genome mutations by infecting at a higher MOI.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments have previously shown that HSV-1 infection at differing MOI yields differential viral gene transcription rates [ 26 , 47 ]. Using our model, we sought to evaluate whether the virus can mitigate the effects of genome mutations by infecting at a higher MOI.…”
Section: Resultsmentioning
confidence: 99%
“…The major capsid protein VP5 (ICP5) and the inner tegument protein UL37 recruit the dynein motor and other accessory proteins such as BICD2, EB1, and the dynactin complex (DCTN) to facilitate retrograde transport of virion capsids. AKt and PKC activities are required for efficient entry and transport along the microtubules towards the nucleus, where the virus replicates its DNA (Adapted from Ralph et al ., 2017, (89)).…”
Section: Discussionmentioning
confidence: 99%
“…These three papers (Sekine et al, 2017;Alandijany et al, 2018;Dembowski and DeLuca, 2018) used three different methods to initiate infection and determine the initial time of infection. This emphasizes the need for an accepted synchronization method for recognizing initial events of incoming viral genomes (Ralph et al, 2017).…”
Section: Initial Interactions Of Viral Genomes With Viral and Host Proteins In The Nucleusmentioning
confidence: 99%
“…Currently, one of the best way to synchronize nuclear entry is using the tsB7 mutant (or its derivatives), which permits the capsids to bind the nuclear pore complex at high temperature but allows rapid injection of viral genome into the nucleus only at low temperature (Batterson et al, 1983;Abaitua et al, 2009;Abaitua et al, 2011;Ralph et al, 2017). However, these temperature changes might affect other viral or host processes (Ralph et al, 2017). Alternative approaches for synchronizing nuclear entry are needed.…”
Section: Future Trendsmentioning
confidence: 99%